LPIC-1 Linux Professional Institute Certification study guide : exams 101-400 and 102-400 - Bresnahan, Christine; Blum, Richard (Sybex, 2015)
The LPIC-1 Linux Professional Institute Certification Study Guide, 4th Edition is your one-stop resource for complete coverage of Exams 101-400 and 102- 400. This Sybex Study Guide covers 100% of all exam 101-400 and 102-400 objectives. You'll prepare for the exams smarter and faster with Sybex thanks to superior content including, assessment tests that check exam readiness, objective map, real-world scenarios, hands-on exercises, key topic exam essentials, and challenging chapter review questions. Reinforce what you have learned with the exclusive Sybex online learning environment, assessable across multiple devices. Get prepared for the LPIC-1 Exams 101-400 and 102-400 with Sybex.